Acoustic and visual pacesetter influence on the energy expenditure in a cycling exercise - Fattorini, L.; Rodio, A. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The aim of this study was to evaluate the effects of acoustic and visual pacesetters on the energy expenditure in a steady state 30-minute long cycling. METHODS: Eighteen healthy male subjects (age 27.6±4.59 years; height 1.78±0.07 m; body mass 80.1±7.85 kg) performed a 30-minute submaximal exercise at a constant workload on a cycle ergometer. The imposed workload required a metabolic expenditure corresponding to 70% of ventilatory threshold for each subject. Energy expenditure - expressed as a caloric equivalent relative to the total net oxygen consumption during exercise - was evaluated using three conditions: control (CT), no external pacesetter; acoustic (AT), listening to rhythmic acoustic stimuli at 120 beat per minute; and visual (VT), seeing footage consisting of eight different images in a looped sequence at 120 frames per minute. RESULTS: All measured parameters qualified the exercise as requiring mainly an aerobic metabolism, showing no pain and no fatigue. AT and VT energy expenditure (5.0±0.44 and 4.9±0.39 MET respectively) were significantly lower compared to CT (5.5±0.49 MET), while no difference between AT and VT were recognized. CONCLUSIONS: This study confirmed the ergogenic effect of the acoustic pacesetter on a 30-minute steady state rhythmic exercise. Novelty is that the visual pacesetter too was able to increase the mechanical efficiency as the same manner than the acoustic one. The present setting adopting visual pacesetter could be used in special categories, such as the deaf or in innovative technological tools as head-mounted display devices.